Reservoir optimization with differential evolution - Phuong, Phan Thi Thu; Lai, Hoang Van; Tri, Bui Dinh (Vietnam Journal of Mechanics, 2016)
Reservoir optimization, is one of recent problems, which has been researched by several methods such as Linear Programming (LP), Non-linear Programming (NLP), Genetic Algorithm (GA), and Dynamic Programming (DP). Differential Evolution (DE), a method in GA group, is recently applied in many fields, especially water management. This method is an improved variant of GA to converge and reach to the optimal solution faster than the traditional GA. It is also capable to apply for a wide range space, to a problem with complex, discontinuous, undifferential optimal function. Furthermore, this method does not requirethe gradient information of the space but easily find the global solution by asimple algorithm. In this paper, we introduce DE, compare to LP which was considered mathematically decades ago to prove DE’s accuracy, then apply DE to Pleikrong, a reservoir in Vietnam, then discuss about the results.